First-line systemic therapy in patients with metastatic or locally advanced urothelial carcinoma: a systematic review and network meta-analysis of randomized controlled trials - Yandong Xie; Haoyang Liu; Yanfeng Tang; Yaowen Zhang; Nanwei Xu; Fengnian Zhao; Jinge Zhao; Guangxi Sun; Zhenhua Liu; Pengfei Shen; Hao Zeng; Junru Chen (Therapeutic Advances in Medical Oncology)
Background: The emergence of immune checkpoint inhibitors and antibody–drug conjugates has revolutionized the first-line treatment landscape for locally advanced or metastatic urothelial carcinoma (la/mUC). However, the optimal treatment strategy remains uncertain. Objectives: This network meta-analysis (NMA) aimed to evaluate the efficacy and safety of various first-line treatments for la/mUC. Design: Systematic literature review with a Bayesian NMA. Data Sources and Methods: Eligible studies were retrieved from PubMed, EMBASE, and Web of Science, with a search cutoff of July 2024. Randomized controlled trials (RCTs) evaluating first-line treatments for la/mUC were included. Pairwise comparisons and Bayesian NMA were conducted to compare overall survival (OS) and progression-free survival (PFS) using hazard ratios (HR) and 95% credible intervals (CrIs), and objective response rate (ORR) and treatment-related adverse events (TRAEs) using odds ratios and 95% CrIs. Results: In total, 17 articles involving 11 RCTs and 7586 patients were included. Enfortumab vedotin (EV) plus pembrolizumab demonstrated the most significant improvement in OS (HR 0.47, 95% CrI 0.38–0.58) compared to platinum-based chemotherapy in the overall populations, with consistent benefits across cisplatin-eligible, cisplatin-ineligible, and PD-L1-positive/negative subgroups. EV plus pembrolizumab also ranked highest for PFS (HR 0.45, 95% CrI 0.38–0.54) and had a favorable ORR compared to other regimens. In terms of safety, atezolizumab monotherapy exhibited the lowest incidence of high-grade TRAEs, EV plus pembrolizumab had higher overall TRAE rates but lower rates of grade 3 or higher TRAEs than platinum-based chemotherapy and nivolumab plus gemcitabine–cisplatin. Conclusion: This NMA provides the most comprehensive analysis of first-line treatments for la/mUC, integrating the latest clinical data. EV plus pembrolizumab demonstrated superior efficacy and acceptable safety profiles in overall and subgroup analyses, establishing it as a promising treatment option. Trial registration: The study was registered in PROSPERO (CRD42024502320).